2018
DOI: 10.3928/19404921-20180502-01
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Support and Telemonitoring for Low-Income Older Adults

Abstract: The objective of the current pilot study was to determine whether nurse-led telephone counseling improves health behavior, self-care, and physiological indices for low-income older adults using a telemonitoring system. The control group (n = 15) was provided with weekly health education only, and the intervention group (n = 20) was given additional telephone support by nurses. At baseline and 8 weeks, data on health and self-care behaviors were collected using a self-reported questionnaire, and blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 29 publications
1
31
0
2
Order By: Relevance
“…As shown in the data summary table, this included four literature reviews [19][20][21][22], and one Cochrane review [23]. The quantitative studies ranged from randomised controlled trials and interventions [24,25] to, pre and post-test interventions [26][27][28] to cross sectional and longitudinal studies [29][30][31][32][33][34][35][36] to studies that employed surveys and questionnaires [37,38] and analysis of case records [39,40]. There were three mixed method studies [41][42][43] that drew on existing call centre data and interviews, as well as six qualitative studies.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in the data summary table, this included four literature reviews [19][20][21][22], and one Cochrane review [23]. The quantitative studies ranged from randomised controlled trials and interventions [24,25] to, pre and post-test interventions [26][27][28] to cross sectional and longitudinal studies [29][30][31][32][33][34][35][36] to studies that employed surveys and questionnaires [37,38] and analysis of case records [39,40]. There were three mixed method studies [41][42][43] that drew on existing call centre data and interviews, as well as six qualitative studies.…”
Section: Methodsmentioning
confidence: 99%
“…Supporting the need for a protocol, Derkx et al [35] found that some nurses made decisions about the patient's condition before all the relevant clinical information was gathered, highlighting the need for appropriately prepared nurses and reinforcing that both the use of protocols and the clinical experience of the services provider (usually a registered nurse) are essential elements for phone-based triage/support. The research reported by Jeong et al [25] includes a description of the development of an algorithm developed for the specific needs of their target population.…”
Section: Cariello F 2000mentioning
confidence: 99%
See 3 more Smart Citations